Diversity and Distribution of Macrofungi in the Mid-hills of Bagmati Province, Central Nepal - Adhikari, Hari Sharan; Shrestha, Suman; Gurung, Manoj; Pandit, Sushma; Balami, Sujan (UI Scholars Hub, 2025)
The current study was carried out at seven research sites in the mid-hills (900-2500m asl) across six districts in Bagmati province, central Nepal to analyze the variety and distribution of macrofungal communities. The survey was carried out in the wet seasons from August 2017 to September 2022, including frequent field visits to the selected forests. Vari-ous diversity indices were applied to ascertain the composition of the macrofungal communities in the study area. A total of 133 wild macrofungal species belonging to 80 genera, 50 families, and 19 orders were observed. The macro-fungal population in the Bagmati province was dominated by Russula (10 spp.) and the family Russulaceae (14 spp.). Additionally, 50 edible, 28 inedible, and 12 potentially medicinally-mushrooms have been identified. With 75 species, humicolous macrofungi dominated all others, followed by lignicolous ones (48 spp.). A majority of the species (50) were edible, whereas the numbers of medicinal and poisonous ones were 11 and 6 respectively. Based on their ecology, the saprobic and mycorrhizal macrofungi were predominant at 67 and 45 species, respectively. The diversity indices varied from 19 to 40 (richness), 3.68 to 7.79 (Margalef), 0.91 to 0.98 (Simpson’s dominance), 0.28 to 0.36 (Shannon–Wiener’s diversity) and 0.056 to 0.074 (evenness). The results of this study indicated that several macrofungi might be employed as foods and alternative medicines requiring more studies. This study further contributes to the existing data on mushroom diversity in the Bagmati province of Nepal.